2014
DOI: 10.1097/icb.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Headache and Whiteout Vision as the Presenting Symptoms in a Case of Takayasu Retinopathy

Abstract: Up to one third of patients with Takayasu disease experience visual disturbances, and as a result, ophthalmologists may be the first physicians to encounter and diagnose this condition. The various stages of Takayasu retinopathy are characterized by dilation of small vessels, capillary microaneurysm formation, and development of arterial-venous anastomoses. The initial clinical presentation of Takayasu disease can be varied and nonspecific, therefore a high index of clinical suspicion is essential for diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Among them, 2 were written in Chinese (6 patients) (18,25), and the remaining 47 (59 patients) were published in English. Included studies were published between 1957 and 2021, the types of which were case reports (40 articles) (7,8,16,17,19,, case series (7 articles) (3,17,18,20,(59)(60)(61), and image-based articles (2 articles) (21,62). The methodological quality assessment showed that 8 studies were of good quality, 33 studies were of moderate quality, and 8 studies were of poor quality (Supplementary Table 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 2 were written in Chinese (6 patients) (18,25), and the remaining 47 (59 patients) were published in English. Included studies were published between 1957 and 2021, the types of which were case reports (40 articles) (7,8,16,17,19,, case series (7 articles) (3,17,18,20,(59)(60)(61), and image-based articles (2 articles) (21,62). The methodological quality assessment showed that 8 studies were of good quality, 33 studies were of moderate quality, and 8 studies were of poor quality (Supplementary Table 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Compared with open surgery, angioplasty with or without stent is a less invasive and safe method, especially for short-segment lesions (15). Over the past decades, sporadic case reports have addressed ocular outcomes in surgery-treated TA patients (16)(17)(18)(19). A recent case-series study (20) specifically reported the efficacy of endovascular stenting in TR patients.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary material 4 gives details of the studies included for analysis of various parameters. [ 2 3 5 6 7 8 11 12 13 14 15 17 18 19 20 26 29 30 31 32 33 34 35 36 38 39 40 41 42 44 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 65 66 68 69 70 71 72 74 75 76 77 78 83 84 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] In addition to the age and effect of steroids, the circulatory alterations causing diminished lens nutrition, metabolic changes, and possibly neuroreceptor derangement favor cataract formation. [ 10 11 12 ] Findings such as iris atrophy, anterior chamber (AC) flare, and intraoperative incalcitrant hyphema in the absence of neovascularization at the iris or angle indicate chronic anterior segment ischemia causing early cataract changes. [ 10 ]…”
mentioning
confidence: 99%
“…7 Ocular symptoms are also vague and includes amaurosis fugax, visual disturbances, subjective reduction in vision, or patients may be asymptomatic. [8][9] Approximately 25.7% of patients with Takayasu arteritis experiences amaurosis fugax. 10 As the disease advances, a decrease in intraocular pressure may also be noted.…”
Section: Signs/symptomsmentioning
confidence: 99%